2017
DOI: 10.1587/transinf.2016edp7383
|View full text |Cite
|
Sign up to set email alerts
|

A High Performance FPGA-Based Sorting Accelerator with a Data Compression Mechanism

Abstract: SUMMARYSorting is an extremely important computation kernel that has been accelerated in a lot of fields such as databases, image processing, and genome analysis. Given that advent of Internet of Things (IoT) era due to mobile technology progressions, the future needs a sorting method that is available on any environment, such as not only high performance systems like servers but also low computational performance machines like embedded systems. In this paper, we present an FPGA-based sorting accelerator combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It has been shown that although very appreciable results have already been achieved, with various authors proving the benefits of reconfigurable hardware implemen-tations compared to software solutions, more work is still required in particular in the scope of exploring high-level synthesis potential and reducing the communication bottleneck, which is currently the main limiting factor of the majority of the designs. Different proposals have been carried out to mitigate the bandwidth limitation, such as communication-time data processing [32] and a data compression mechanism [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that although very appreciable results have already been achieved, with various authors proving the benefits of reconfigurable hardware implemen-tations compared to software solutions, more work is still required in particular in the scope of exploring high-level synthesis potential and reducing the communication bottleneck, which is currently the main limiting factor of the majority of the designs. Different proposals have been carried out to mitigate the bandwidth limitation, such as communication-time data processing [32] and a data compression mechanism [51].…”
Section: Discussionmentioning
confidence: 99%
“…A common approach is the calculation of differences between values [16], [17], [18], [19], [20]. These differences may be between sampled data and a model [16] or between sampled data and a reference value (base) [17], [18] or between consecutive samples [16], [18], [19]. When dealing with signal traces, which are sampled at rates high enough that consecutive samples have values close to each other, i.e.…”
Section: Overview Of Available Solutionsmentioning
confidence: 99%
“…closer to zero, with shorter sequences. This approach is quite similar to the one presented in [18], where one sample works as base value and the following three samples undergo the differencing treatment. The base value can be chosen arbitrarily.…”
Section: Operating Principlementioning
confidence: 99%
See 1 more Smart Citation
“…The hardware acceleration technique is a method used to reduce the computational load of a system. This technique migrates some or all of the tasks that the CPU has performed to a hardware device such as a GPU [16], an ASIC [17], or an FPGA [17]- [23]. Some previous researches studied compression acceleration techniques and achieved high bandwidth by parallelizing frequently performed operations [20]- [22].…”
Section: Introductionmentioning
confidence: 99%